THE STATE CADASTRE FOR THE REGULATION OF INFORMATION RESOURCES FOR THE FORMATION AND IMPROVEMENT - Alakhanov , Zokir Mukhriddinkhonovich; Yokubov , Sherzodbek Shavkat o‘g‘li; Olimova , Durdona Shuhratbek qizi (Educational Research in Universal Sciences, 2022)
Based on the socio-economic reforms implemented in our republic and the national model of development based on this, systematic analysis, analogues, mutual comparison, comparative analysis and calculation methods are widely used in the article.